The impact of intrinsic and extrinsic factors on the epidemiology of male-killing bacteria - Fisher, A; Knell, R; Price, T; Bonsall, MB (Wiley, 2022)
Many arthropod species are vulnerable to infection by bacteria that kill the male offspring of their female hosts. These male-killing bacteria (MKB) can greatly impact the ecology and evolution of their hosts, particularly when MKB prevalence is high and persistent through time. However, we still do not have a holistic understanding of the key determinants of MKB ecological epidemiology, particularly regarding the interplay between host-MKB traits and environmental conditions. Here, we derived a mathematical model to analyse the role that several intrinsic and extrinsic factors play in determining MKB epidemiology, and how these factors interact with one another. We found that the invasion threshold and prevalence of MKB is determined by transmission rate and the rate at which female hosts recover from MKB infections. The invasion and prevalence of MKB is also highly sensitive to the extent that MKB can reduce intra-brood competition by killing male offspring. Environmentally-induced periodic changes to the epidemiological characteristics of MKB caused a sharp decline and a slow recovery of MKB prevalence and, in some cases, environmental disturbance can drive MKB extinct. Furthermore, the magnitude of the impact that environmental disturbance had on the dynamics of MKB prevalence was heavily modulated by intrinsic factors, particularly intra-brood competition. This is the first study to explore how both intrinsic and extrinsic factors interact to influence the dynamics of MKB infections over large timescales; our findings are central to predicting the current and future impacts of MKB on host populations.